Formação de mudas de alface em bandejas preenchidas com diferentes substratos - Silva, Ernani Clarete da; Queiroz, Roberto Luiz [UNESP] (Univ Federal Uberlandia, 2014)
This study was conducted in the Department of Horticulture and Experimentation at the University Jose do Rosario Vellano (UNIFENAS) in Alfenas-MG, Brasil in order to evaluate the formation of lettuce seedlings in trays filled with different substrates. The materials used to compose the substrates were pig bed base with wood shavings (M), pig bed with base coffee straw (C), earthworm humus (H) and commercial substrates Nutriorg (R) and Plantmax (R) The use of these pure substrates and various mixtures permitted the formation of 18 substrates that constituted the treatments. The experimental design was a completely randomized design with three replications. The lettuce seedlings were formed with the lettuce cultivar Regina. The seeds were sown in trays with 128 cells filled with the substrates under study. Each experimental unit was compost of 64 cells. The conduct of the experiment was within a protective structure of 85 m 2, model chapel with transparent plastic cover 100 microns thickness, additives against ultraviolet rays. After 30 days of sowing, ten seedlings were harvested randomly within each experimental unit for evaluating the number of leaves and the plant height. It was also evaluated the fresh and dry mass of aerial part and fresh and dry mass of root. It was concluded that the substrate T1 - M met the best features for the formation of lettuce seedlings in trays of 128 cells.

O presente trabalho foi conduzido no Setor de Olericultura e Experimentação da Universidade José do Rosário Vellano (UNIFENAS), no município de Alfenas - MG, Brasil, com o objetivo de avaliar a formação de mudas de alface em bandejas preenchidas com diferentes substratos. Os materiais usados para compor os substratos foram a cama de suínos com base de maravalha (M), cama de suínos com base de palha de café (C), húmus de minhoca (H) e os substratos comerciais Nutriorg® e Plantmax®. O uso puro destes substratos e várias misturas possibilitaram a formação de 18 substratos que constituiram os tratamentos. O arranjo experimental foi o delineamento inteiramente ao acaso, com três repetições. As mudas de alface formadas foram da cultivar Regina. A semeadura foi realizada em bandejas de isopor com 128 células, preenchidas com os substratos em estudo, sendo cada unidade experimental formada por 64 células. A condução do experimento foi dentro de uma estrutura de proteção de 85 m2, modelo capela, com cobertura de plástico transparente de 100 micra de espessura, aditivada contra raios ultravioletas. Aos 30 dias do semeio, foram colhidas dez plântulas, ao acaso, dentro de cada unidade experimental, para avaliar o número de folhas e a altura das plantas. Também foram avaliadas as massas fresca e seca da parte aérea e massas fresca e seca da raiz. Concluiu-se que o substrato T1 –M reuniu as melhores características para a formação de mudas de alface em bandejas de isopor de 128 células.
Formation of lettuce seedlings in trays filled with different substrates
Keywords: Lactuca sativa; Organic residues; Plant propagation